(untitled) (Journal of Science and Technology, 2016)
This paper analyses some of the passable, albeit unacceptable, uses of English in academia and draws attention to the need to be conscious of the deviances. Some recurrent words and phrases have been picked from utterances of teachers, articles by journalists and essays of students for the study. The point is also made that, like Chinua Achebe (1974) who would seize an opportunity to remove ‘structural weaknesses\’ from his Arrow of God, intellectuals should not see the acquisition of high qualifications as being necessarily the quintessence of knowledge, nor should deviant use of English be accepted in the name of so-called innovation. The dictionary form has been used to facilitate easy reference.